Pandemic Responses in Chinua Achebe’s Short Story “The Sacrificial Egg” - Chapai, Udaya; Sharma, Prakash (Pragnya Sarathi प्रज्ञा-सारथि, 2025)
This paper examines and analyzes the causes of the Smallpox pandemic and people's responses toward it in Chinua Achebe’s short story “The Sacrificial Egg”. The smallpox pandemic has damaged various dimensions of Umuru, including its place and people. The busy port bears its degradation and contamination along with Western encroachment. Umuru people follow the Churches and their education after their colonization. The new generation disobeys their elders and disrespects their traditional deities. As revenge, the evil deity Kitikpa incarnates in the form of smallpox. As a result of the pandemic, the sprawling, busy, and crowded Nkwo market turns into silence under the ruling strength of flies. Smallpox as a colonial gift breaks and stops usual activities. Everything turns into a vast emptiness. Consequently, it claims that a catastrophic smallpox pandemic affects human activities and people respond variously to it. It aims to discuss issues like flight and flee, violence and rituals, piety and cults, and social distancing and lockdown as responses to the pandemic. In this context, following qualitative research design, this paper employs critical, interpretative, and analytical methods to attain the claim. Picking up lines and ideas from the primary text, interpretation and analysis support the arguments. It concludes with how pandemic literature deals with terrific human experiences.